1977
DOI: 10.1084/jem.146.2.520
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic modulation of Friend virus erythroleukemic cells in vitro by serum from mice with dormant erythroleukemia.

Abstract: In the tumor dormant state, small numbers of tumor cells persist in the host without outgrowth to overt neoplasia. The cancer literature contains numerous reports describing recurrence of solid tumors and leukemias years after apparent successful treatment of the primary neoplasia (1). These reports suggest that residual tumor cells can persist in a dormant state during the prolonged clinical remission. Few experimental models have been developed to study the tumor dormant state. In this laboratory we have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1979
1979
1985
1985

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…We have not been able to detect virus neutralizing antibodies in SFFV ÷ preleukemic mice, but this does not preclude the possibility of rapid development of humoral immunity to MuLV infection. It has been shown that the induction of FV cytotoxic antibodies may be a contributing mechanism in the development of dormant FV infection (33,34) and in the regression of FV disease (35). An important alternative explanation is based upon our previous observation that SFFV may be classified as a DI particle (9).…”
Section: Discussionmentioning
confidence: 99%
“…We have not been able to detect virus neutralizing antibodies in SFFV ÷ preleukemic mice, but this does not preclude the possibility of rapid development of humoral immunity to MuLV infection. It has been shown that the induction of FV cytotoxic antibodies may be a contributing mechanism in the development of dormant FV infection (33,34) and in the regression of FV disease (35). An important alternative explanation is based upon our previous observation that SFFV may be classified as a DI particle (9).…”
Section: Discussionmentioning
confidence: 99%
“…1. As FR-6 was stably resistant to the antibody for more than 6 months, the clone could be a true mutant, but many other cells in the population which resisted the antibody after immunoselection could have been the ones whose target molecules were simply masked in the presence of antibody as in antigenic modulation of FLC-745 cells (Genovesi et al, 1977) or TL cells (Old et al, 1968). We recently observed that the virus non-producers obtained above formed large aggregates spontaneously when mixed with virus-producing parental cells and the virus producers in such aggregates appeared to resist complement-dependent cytotoxicity.…”
Section: Short Communicationmentioning
confidence: 99%
“…under conditions of growth inhibition While modulation of FLV gp71 expression on leukemia cells exposed to appropriate antisera without C' in vitro or in vivo has been described in the absence of any significant effects on cell replication and/or growth (Genovesi et al, 1977;Callahan et al, 1980;Stackpole et al, 19801, in a n attempt to elucidate the mechanism of the antibody-mediated growth inhibition described above it was decided to determine whether antigenic modulation occurs under these conditions. FLC-745 cells were cultured in inhibitory medium containing 185 pglml of GaFLV gp71 IgG or control medium containing 225 pg/ ml of NGS IgG, and viable cells from each culture were tested for susceptibility to lysis by exogenous C' alone or by fresh AGaFLV gp71 serum + C'.…”
Section: Modulation Of Flv Gp71 Expression On Flc-745 Cellsmentioning
confidence: 99%